2015
DOI: 10.1128/aac.00072-15
|View full text |Cite
|
Sign up to set email alerts
|

Robust Algorithm for Systematic Classification of Malaria Late Treatment Failures as Recrudescence or Reinfection Using Microsatellite Genotyping

Abstract: Routine therapeutic efficacy monitoring to measure the response to antimalarial treatment is a cornerstone of malaria control. To correctly measure drug efficacy, therapeutic efficacy studies require genotyping parasites from late treatment failures to differentiate between recrudescent infections and reinfections. However, there is a lack of statistical methods to systematically classify late treatment failures from genotyping data. A Bayesian algorithm was developed to estimate the posterior probability of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…A recent publication (17) presented a statistical method based on Bayesian probability to analyse microsatellite data to calculate drug failure rates. This method generates the posterior probability that a recurrent infection is a recrudescence and has subsequently been used to analyse TES data (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication (17) presented a statistical method based on Bayesian probability to analyse microsatellite data to calculate drug failure rates. This method generates the posterior probability that a recurrent infection is a recrudescence and has subsequently been used to analyse TES data (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…6). Previous studies indicated links between parasite virulence 38,46 , parasite numbers at time of treatment 38,46 , and treatment duration 38,46 as influencing frequency of recrudescence for different Plasmodium parasites. Overall, these findings suggest, that the current mechanistic models do not provide additional structural insight to late recrudescence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dried blood spots were collected on Whatman 903 filter paper on D0, D3, D7, D14, D21, D28 and at any unscheduled visits. Fragment lengths of seven neutral microsatellite markers (Supplemental Table S1) were used to compare genotypes on D0 and day of failure for patients with recurrent parasitemia using a Bayesian classifier for molecular correction [28]. In brief, the Bayesian algorithm uses allele frequencies to calculate the posterior probability of recrudescence for each recurrent parasitemia.…”
Section: Biomolecular Markersmentioning
confidence: 99%